1994
DOI: 10.1093/oxfordjournals.jbchem.a124628
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nucleolin as a Binding Protein for Midkine (MK) and Heparin-Binding Growth Associated Molecule (HB-GAM)1

Abstract: Midkine (MK) is a heparin-binding growth/differentiation factor with a molecular weight of 13 kDa, and is structurally unrelated to fibroblast growth factors (FGF). We studied MK-binding proteins in order to clarify the action mechanism of MK. A 100-kDa protein was identified in PYS-2, 3T3, and L cells as an MK-binding protein by a ligand blot experiment. This MK-binding protein was purified by affinity chromatography on an MK-agarose column followed by SDS polyacrylamide gel electrophoresis. Sequence determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 0 publications
3
79
0
3
Order By: Relevance
“…Enamel organ formation and cell differentiation were both inhibited in cultured tooth germ by adding the neutralizing antibodies for MK to the culture media (38), thus showing the MK to be an indispensable factor for tooth germ development. Previous reports indicated that the cell surface localized nucleolin proteins act as the receptor of MK (16,25). No other functional role of nucleolin on the transcriptional regulation of MK has been reported.…”
Section: Discussionmentioning
confidence: 94%
“…Enamel organ formation and cell differentiation were both inhibited in cultured tooth germ by adding the neutralizing antibodies for MK to the culture media (38), thus showing the MK to be an indispensable factor for tooth germ development. Previous reports indicated that the cell surface localized nucleolin proteins act as the receptor of MK (16,25). No other functional role of nucleolin on the transcriptional regulation of MK has been reported.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, the exogenously added MK were able to induce neither spontaneous detachment from the substratum nor anchorage-independent growth in the present study. MK has also been reported to bind to nucleolin, a shuttle protein between the nucleus and the cytoplasm (Take et al, 1994). There is a possibility that concerted action of the extracellular MK form and the intracellular MK form is required for cellular transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation and characterization of affinity-purified rabbit anti-mouse MK polyclonal antibodies, which were raised against L cell-produced MK, were described previously . Affinity-purified rabbit polyclonal antibodies against bacteria-produced MK were a generous gift from Dr S Ikematsu and worked as well as the antibodies against cell-produced MK (see Take et al, 1994 for bacteriaproduced MK). Fibronectin expression was examined in the same way as MK expression, using samples prepared from both ITS medium and cell lysates (cells were directly lysed with the SDS-PAGE sample buffer).…”
Section: Western Northern and Southern Blot Analysesmentioning
confidence: 99%
“…On the other hand, although the binding of MK to heparan sulfate and chondroitin sulfate proteoglycans could be clearly demonstrated using purified and soluble components (17,18), the cell surface receptor for MK is not yet clearly identified. For the purpose of characterizing MK receptor, nucleolin has been isolated by purification of crude cell extracts using an MK affinity matrix column (19). By using a solid-phase binding assay, recently evidence has been provided to show that protein-tyrosine phosphatase binds MK with high affinity (20).…”
mentioning
confidence: 99%